1981
DOI: 10.1017/s0022112081003480
|View full text |Cite
|
Sign up to set email alerts
|

The time-dependent deformation of a capsule freely suspended in a linear shear flow

Abstract: An analysis is presented of the dynamics of a small deformable capsule freely suspended in a viscous fluid undergoing shear. The capsule consists of an elastic membrane which encloses another viscous fluid, and it deforms in response to the applied external stresses and the elastic forces generated within the membrane. Equations are derived which give its time-dependent deformation in the limit that the departure of the shape from sphericity is small. The form of the shear flow is arbitrary and a general (two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
229
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 275 publications
(237 citation statements)
references
References 15 publications
8
229
0
Order By: Relevance
“…Barthes-Biesel and colleagues (Barthes-Biesel and Rallison, 1981;Barthes-Biesel and Sgaier, 1985) studied the motion of an elastic capsule in a linear shear flow under the small deformation regime using perturbation analysis, and obtained the deformation and orientation of the capsule in the shear field. Deformation was found to increase with an increase in the capillary number.…”
Section: Introductionmentioning
confidence: 99%
“…Barthes-Biesel and colleagues (Barthes-Biesel and Rallison, 1981;Barthes-Biesel and Sgaier, 1985) studied the motion of an elastic capsule in a linear shear flow under the small deformation regime using perturbation analysis, and obtained the deformation and orientation of the capsule in the shear field. Deformation was found to increase with an increase in the capillary number.…”
Section: Introductionmentioning
confidence: 99%
“…Perturbation methods were used in the first models of fluid-capsule interactions. Assuming an initially unstressed spherical capsule with a quadratic strain energy function, linearized equations were solved to obtain the steady-state shape 16 and time evolution 17,18 of capsules in simple flows. Barthes-Biesel and Sgaier 19 used linear theory to study the effect of membrane viscosity and found that purely viscous membranes tumble while particles with viscoelastic membranes orient themselves to the streamlines when the shear rate and relaxation time are of the same order.…”
Section: Introductionmentioning
confidence: 99%
“…1, No.1, 2006 where the shell deformations may be large and where the hydrodynamic forces are due to pressure and viscous shear stresses. When the capsule deformation is small, asymptotic solutions can be developed (12) . To first order in ε, the capsule takes an ellipsoidal shape, inclined at an angle Φ = 45 o with respect to the far field streamlines, while the membrane continuously rotates around the steady profile.…”
Section: Journal Of Biomechanical Science and Engineeringmentioning
confidence: 99%
“…The validation of the numerical results is not easy. One way of doing it is to consider an intitially spherical capsule subjected to vanishingly small flow strength and to compare the numerical deformation to the asymptotic analytical deformation (12) developed for that case.…”
Section: Journal Of Biomechanical Science and Engineeringmentioning
confidence: 99%
See 1 more Smart Citation